Conceptualisation of English teachers' professional identity and comprehension of its dynamics. Issue 5 (4th July 2017) - Han, Insuk
Abstract: This study attempts to conceptualise English teachers' professional identity based on an understanding of identity in a socio-psychological framework, and thereby reveal the attributes and dynamics of professional identity by investigating Korean English teachers' cognitive, emotional and behavioural responses to their national English curriculum and related policies. Based on a narrative approach within the qualitative research framework, three modes of narrative were used for data gathering and analysis. Two in-depth interviews were conducted and responses to descriptive questionnaires and metaphor production of a teacher-self required of five academic high school English teachers. Examination of those data disclosed that seven different identities constitute their professional identity, and these identities and their meaning systems interplay within a self, as well as interact with an English language teaching environment. Conceptualisation of English teachers' professional identity and comprehension of its dynamics may help policy-makers or curriculum designers comprehend the mechanisms and rationales of policy success or failure in relation to teacher roles and values, and furthermore will provide several implications to consider for successful curriculum reform.